1998
DOI: 10.1037/0022-3514.74.3.646
|View full text |Cite
|
Sign up to set email alerts
|

Collective identification and social movement participation.

Abstract: Determinants of collective behavior, as suggested by the social identity or self-categorization approach and social movement research, were examined in 2 field studies. Study 1 was conducted in the context of the older people's movement in Germany and Study 2 in the context of the gay movement in the United States. Both studies yielded similar results pointing to 2 independent pathways to willingness to participate in collective action; one is based on cost-benefit calculations (including normative considerati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

30
532
6
18

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 536 publications
(640 citation statements)
references
References 37 publications
30
532
6
18
Order By: Relevance
“…Our model also provides a more general and potentially more parsimonious view of collective action in relation to the Simon et al (1998) and Klandermans (1997) approaches. These models have a clear instrumental component but lack a detailed emotional analysis, and they focus primarily on activism within social movements.…”
Section: Discussionmentioning
confidence: 99%
“…Our model also provides a more general and potentially more parsimonious view of collective action in relation to the Simon et al (1998) and Klandermans (1997) approaches. These models have a clear instrumental component but lack a detailed emotional analysis, and they focus primarily on activism within social movements.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, social psychological research has uncovered the facilitative role of collective identification in mobilization for political action in various social movement contexts, including the women's movement, the older people's movement, the gay movement, the fat acceptance movement, the farmers' movement and right-wing political movements (e.g. De Weerd & Klandermans, 1999;Kelly & Breinlinger, 1996;Simon et al, 1998; for reviews, see Simon, 2004;Stürmer & Simon, 2004;Wright, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, social psychological research has uncovered the facilitative role of collective identification in mobilization for political action in various social movement contexts, including the women's movement, the older people's movement, the gay movement, the fat acceptance movement, the farmers' movement and right-wing political movements (e.g. De Weerd & Klandermans, 1999;Kelly & Breinlinger, 1996;Simon et al, 1998; for reviews, see Simon, 2004;Stürmer & Simon, 2004;Wright, 2001).Although the motivation to support a social movement is rarely free from cost-benefit calculations revolving around more tangible interests of the individual and his or her group (Klandermans, 1997), recent research also indicates that collective identification possesses a unique mobilizing power over and above such calculative considerations (Simon, 2004;Stürmer & Simon, 2004). In a first attempt to uncover the psychological process underlying the mobilizing power of collective identification, Stürmer, Simon, Loewy and Jörger (2003) predicted and found that a sense of inner obligation to…”
mentioning
confidence: 99%
“…If the individual's expectations are high that it is possible to alter politics and have an impact on social structures, protest is more likely to occur. The same holds true for collective identities and feelings of belonging to certain groups or organisations; these might foster protest participation as well (Simon, B. et al 1998). Moreover, emotions also play an important role in the perception of protest events, for instance the degree to which one feels comfortable with the protest venue and form.…”
Section: The Transformation Of Labour Protestmentioning
confidence: 99%